A musculoskeletal modelling approach to explain sit-to-stand difficulties in older people due to changes in muscle recruitment and movement strategies. (2nd January 2020) - Smith, Samuel H.L.; Reilly, Peter; Bull, Anthony M.J.
Abstract: By 2050 the proportion of over 65s is predicted to be 20% of the population. The consequences of an age-related reduction in muscle mass have not been fully investigated and, therefore, the aim of the present study was to quantify the muscle and joint contact forces using musculoskeletal modelling, during a sit-to-stand activity, to better explain difficulties in performing everyday activities for older people. A sit-to-stand activity with and without the use of arm rests was observed in ninety-five male participants, placed into groups of young (aged 18–35 years), middle-aged (aged 40–60 years) or older adults (aged 65 years and over). Older participants demonstrated significantly lower knee extensor and joint forces than the young when not using arm rests, compensating through elevated hip extensor and ankle plantarflexor muscle activity. The older group were also found to have higher shoulder joint contact forces whilst using arm rests. This tendency to reorganise muscle recruitment to include neighbouring groups or other parts of the body could make everyday activities more susceptible to age-related functional decline. Reductions in leg strength, via age- or atrophy- related means, creates increased reliance on the upper body and may result in further lower limb atrophy through disuse. The eventual decline of upper body function reduces strength reserves, leading to increased vulnerability, dependence on others and risk of institutionalisation.